The Impact of Digital Transformation on Business Models and Competitive Advantage - Agustian, Kresnawidiansyah; Mubarok, Endang Saefuddin; Zen, Agustian; Wiwin, Wiwin; Malik, Aulia Januar (PT. LITERASI SAINS NUSANTARA, 2023)
Digital transformation has become a dominant trend in the business world in recent years. The rapid development of information and communication technology has enabled organisations to change the way they operate, interact with customers, and compete in the market. This research aims to analyse the impact of digital transformation on business models and competitive advantage. This research is a literature review that uses a qualitative approach, which implies that data will be analysed and interpreted using information and text obtained from various sources. The study results show that in the ongoing era of digital transformation, its impact on business models and competitive advantage is an aspect that cannot be ignored. This digital transformation has changed the fundamentals of how organisations operate and interact with customers, and how they can win the competition in an increasingly fierce market. Digital transformation has brought about a significant business paradigm shift. Today, more organisations are integrating digital technology as an integral part of their business model. It is no longer an option, but a necessity to maintain relevance and competitiveness in the market.